Continuous theta burst stimulation over the bilateral supplementary motor area in obsessive-compulsive disorder treatment: A clinical randomized single-blind sham-controlled trial. Issue 1 (7th October 2022) - Guo, Qihui; Wang, Kaifeng; Han, Huiqin; Li, Puyu; Cheng, Jiayue; Zhu, Junjuan; Wang, Zhen; Fan, Qing
Abstract: Background: Obsessive-compulsive disorder (OCD) can cause substantial damage to quality of life. Continuous theta burst stimulation (cTBS) is a promising treatment for OCD patients with the advantages of safety and noninvasiveness. Objective: The present study aimed to evaluate the treatment efficacy of cTBS over the bilateral supplementary motor area (SMA) for OCD patients with a single-blind, sham-controlled design. Methods: Fifty-four OCD patients were randomized to receive active or sham cTBS treatment over the bilateral SMA for 4 weeks (five sessions per week, 20 sessions in total). Patients were assessed at baseline (week 0), the end of treatment (week 4), and follow-up (week 8). Clinical scales included the YBOCS, HAMD24, HAMA14, and OBQ44 . Three behavioral tests were also conducted to explore the effect of cTBS on response inhibition and decision-making in OCD patients. Results: The treatment response rates were not significantly different between the two groups at week 4 (active: 23.1% vs. sham: 16.7%, p = 0.571) and week 8 (active: 26.9% vs. sham: 16.7%, p = 0.382). Depression and anxiety improvements were significantly different between the two groups at week 4 (HAMD24 : F = 4.644, p = 0.037; HAMA14 : F = 5.219, p = 0.028). There was no significant difference between the two groups in the performance of three behavioral tests. The treatment satisfaction and dropout rates were not significantly different between the two groups. Conclusions: The treatment of cTBS over the bilateral SMA was safe and tolerable, and it could significantly improve the depression and anxiety of OCD patients but was not enough to improve OCD symptoms in this study.